Analisis Pengaruh Pemasaran Kreatif, Pengembangan Rute dan Pelayanan Bandara terhadap Peningkatan Jumlah Penumpang - Syahputra, Agung (JURNAL RISET BISNIS DAN MANAJEMEN, 2018)
The purpose of this study is to determine the effect of creative marketing, airport development and service to increase the number of passengers. Methods of research using associative research methods with multiple linear regression analysis techniques. The study population was 60, the sampling technique used purposive sampling where the sample number of 52 respondents were calculated using the slovin formula. The results showed simultaneously creative marketing (X1), development of route (X2) and public service (X3) influenced the increase of Passenger Number (Y), while the partial variable of development of route (X2) and public service (X3) number of passengers (Y) while creative marketing variable (X1) has no significant effect to the increase of Passenger NumberKeywords: creative marketing, route development, Airport services and increased number of passengers